2011
DOI: 10.1093/heapro/dar086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating educational media using traditional folk songs ('lam') in Laos: a health message combined with oral tradition

Abstract: In the Lao People's Democratic Republic (Laos), health education is clearly a core aspect of the health service and is vital in improving people's lives through good health. However, there are many obstacles to conducting effective health education. The development of effective educational media is one solution to these problems. In Laos, traditional folk songs (lam) are preserved as part of the local communication media, and recently this communication medium has been used for health education. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…A similar method was used in a study in Laos which utilized traditional folk songs known as 'lam' as an educational medium for preventing HIV/AIDS 13 . Based on interviews in the focus group discussions, the authors concluded that traditional folk songs could be used to motivate individual behavioural changes and to encourage community action for disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A similar method was used in a study in Laos which utilized traditional folk songs known as 'lam' as an educational medium for preventing HIV/AIDS 13 . Based on interviews in the focus group discussions, the authors concluded that traditional folk songs could be used to motivate individual behavioural changes and to encourage community action for disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The present authors selected the Kawakita Jiro (KJ) method for the analysis of the transcripts (Kawakita, 1996). The KJ method is widely used and accepted for analysis of qualitative research (Nomura et al, 2015;Yoshida, Kobayashi, Sapkota, & Akkhavong, 2012). It involves integrating somewhat disarrayed data and ideas to produce new concepts (Kawakita, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…19 As literacy levels among patients vary substantially, greater incorporation of pictorial images in messages to patients are welcomed additions. Patients are often overwhelmed by the volume and complexity of material that accompanies drug therapies.…”
Section: Discussionmentioning
confidence: 99%